The Impact of Using Songs and Music on English Language acquisition of children in Saudi Arabia - AlAfar, Manahel Abudolmohsen (Arab Journal for Sciences and Research Publishing, 2016)
Aims: To establish the impact of using songs and music on English language acquisition of children in Saudi Arabia Methodology: Descriptive study, involved 20 Saudi teachers with different ages who were randomly selected from governmental and privates schools in Riyadh city - Saudi Arabia. The age of their students ranged from 6 to 10 years. 40 parents volunteered to participate, Parents were asked to answer an online survey comprising ten different questions. The survey was downloaded from the ‘Survey Monkey’ website. Interview questionnaire and online survey were the tools used for data collection. SPSS version 18 was used for data entry and analysis. Results: About 9 of all teachers don’t use songs and rhymes activities in teaching English. 15 of teachers out of 20 said that this technique is not a mandatory part of the curriculum. 13 of the teachers believe that it is very important and 2 teachers believed in using songs and rhymes for facilitate remembering. 16 of teachers out of 20 noticed that their students are actually using the songs or their vocabularies outside the classroom and 17 of all teachers stated that songs and rhymes helped their young learners’ English language development. 82.50% of parents in Saudi Arabia support teaching English to their children, 47.50% of parents stated that their child is using English only in the classroom. Only 7.50% of the parents were not aware of this classroom activity while 92.50% of them are aware. 2.50% of parents expressed their disagreement to use songs and rhymes in teaching English to their young children. Conclusion: Songs and rhymes is rarely used in teaching English to young learners in the Saudi Arabia and curriculum was not rich enough with fun activities like songs and rhymes.